Case Report: A case of primary pericardial mesothelioma treated with multimodal combined therapy - Gong, Jinlan; Wu, Xiaofeng; Wang, Jiehua (Frontiers in Cardiovascular Medicine, 2024)
Background Primary pericardial mesothelioma (PMPM) is a rare, aggressive, and lethal form of cancer. Due to its rarity, low incidence and poor prognosis, PMPM has no accepted standard-of-care treatment options with management and outcomes often extrapolated from diffuse pleural mesothelioma. Disease-specific studies are needed to better define PMPM. We report a case of PMPM highlighting the potential role for multimodal combined therapy. Case report The patient is a 62 years old female who had nonspecific syndromes and inconclusive image findings in May 2023. Then monthly follow-up echocardiography was performed. Two months later, cardiac ultrasound showed pericardial fluid. Pericardiocentesis with pericardial drain was performed. The fluid was bloody, cultivations for tuberculosis were negative and cytological analysis of the fluid showed no malignant cells. Positron emission tomography-computed tomography revealed that the lesion was localized at the anterior and left part of the mediastinum without distant metastasis. Followed up a pericardiectomy was operated. The diagnosis of PMPM is determined by pathological and immunohistochemical evaluation of tissue specimens. Postoperative patient experienced chest pain, right shoulder and upper limb swelling and pain. Pain management and anticoagulant therapy were administered. The patient underwent multimodal therapy consisting of surgical resection, six cycles of chemotherapy (carboplatin plus pemetrexed) in combination with pembrolizumab, and sequential adjuvant intensity-modulated radiation therapy, totaling 50 Gy in 25 fractions, as the first-line treatment, resulting in complete relief of symptoms and satisfactory outcomes with no complications. Presently, the tumor is under local control, with no signs of distant metastasis, and maintenance immunotherapy is scheduled. Continued observation is necessary for monitoring subsequent disease progression. Conclusion PMPM represents a distinct disease with no universally accepted treatment options. The case suggests that multimodal treatment may improve outcomes in selected patients with PMPM.